Alih Fungsi Bangunan Heritage Antico Coffee di Kota Bandung - Sajid, Sriwinarsih Maria Kirana; Yuwono, Astrid Austranti; Josephine, Aracely (Serat Rupa: Journal of Design, 2024)
Buildings inherited from the Dutch East Indies reign are part of the city's development which also enriches the architectural treasures, especially in the city of Bandung. This makes the building a legacy of the Dutch East Indies government, has high historical and aesthetic value which can be a reference for design and architecture science. Changes in the function of the building are carried out as an effort to maintain the building with new activities, so that it able to finance the survival of the conservation building itself. Antico Coffee has changed functions several times and at the time the research was conducted it had the function of a café. The research object is located at the 'new' Bandung residential area which was built around 1921-1924, has a shop building typology that have similarity to the Cihapit shops.  This research aims to conduct an evaluation study of the transfer of function of the research object building in the architectural scope, namely elements related to the building façade; architectural and interior elements; as well as structural and engineering elements of buildings. The research method is descriptive qualitative based on the Alhojaly’s evaluation model. What changes and what parts of the building are maintained so that the building's identity as a building contains historical value during the Dutch East Indies colonial government. The physical character of the building is maintained by making additions to building elements that have been lost, to bring out and strengthen the character of the original building. The benefits of this research provide insight for the community that preservation using a conversion approach can be carried out while maintaining and even strengthening the identity of cultural heritage building elements.